Supportive care of neurodegenerative patients - Armitage, A. E.; Fonkem, E. (Frontiers in Oncology, 2023)
Neurodegenerative illnesses are notorious for paucity of treatment and relentless progression of disease. Illness may be reasonably acute presentation with an aggressive course, for example primary brain tumors such as glioblastoma, or a more insidious onset with a slower but relentless course such as Parkinson’s disease. Regardless, such neurodegenerative diseases are terminal and benefit from the intervention of supportive care for both the patient and the family, in conjunction with primary disease management. Supportive palliative care has been shown to improve quality of life, enhance patient outcomes, and often extend patient life, but such care needs to be tailored. This review examines the role of supportive palliative care in the management of neurologic patients comparing and contrasting glioblastoma patients with idiopathic Parkinson’s disease patients. Both diseases are high utilizers of the healthcare resources, require active management of multiple symptoms and have high caregiver burden underscoring the need for supportive services in conjunction with disease management provided by the primary care team. Although there are many similarities, the differences in palliative patient management are important to appreciate respecting that customizing patient treatments provides the most optimal outcomes. Review of prognostication, patient and family communication, trust and relationship building, and complementary medicinal approaches to well-being are explored for these two diseases which broadly represent two differing poles of incurable neurological illness.